Pozytywny, negatywny czy neutralny? Pytanie o naturę kapitału społecznego - Barczykowska, Agnieszka (Wydawnictwo Naukowe UAM, 2012)
Social capital can be defined as the resource to which people have access through their social relation. Social capital is generally regarded as a good thing. Social group with high social capital have better health, greater education system, less crime and violence. But sometimes social capital can cause crime, illegitimacy, bribery and corruption. This article it’s a question about positive, negative and neutral effect social capital
Positive, negative or neutral? – question about nature of social capital
Keywords: social capital; exclusion; inclusion; crime; social problems; well-being